Sílicas funcionalizadas para reação de transesterificação - Gazola, Fernando César (Universidade Federal de São Carlos, 2019)
Increasing biodiesel production is a worldwide need. Basic homogeneous catalysts are the most widely used by the biodiesel processing industry and present problems such as the need of best quality raw material, high waste generation and large number of biodiesel purification steps. Different heterogeneous catalysts were synthesized aiming to obtain a material with good activity and catalytic stability. Catalysts with acid sites containing DES (deep eutectic solvent) of choline chloride and p-toluenesolfonic acid (ChCl / PTSA) were impregnated in Areosil silica and SBA-15 mesoporous presented good catalytic activity in the transterification of methyl acetate with ethanol, but losing activity in reuse. Dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium hydroxide (TPOAOH) was also prepared and used in the synthesis of basic heterogeneous catalysts by co-condensation and grafting methods, however TPOAOH did not increase the catalytic activity. The other group of heterogeneous acid catalysts was composed of ionic liquids derived from groups of imidazole and sulfonic, whereas the catalysts synthesized by co-condensation with this material did not present catalytic activity, unlike synthesized catalysts by grafting that were active, especially transesterification at 65 ° C, but remain unstable at reuse.
Functionalized silicas for transesterification reaction
Keywords: Transesterificação; Co-condensação; Ancoragem; Imidazol; Sulfônico; Cloreto de colina; Transesterification; Co-condesation; Grafting; Imidazole; Sulfonic; Choline chloride; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura